THE INFLUENCE OF FINANCIAL DISTRESS, MANAGEMENT CHANGE AND CLIENT COMPANY SIZE ON AUDITOR SWITCHING IN LQ45 COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE IN 2019-2021: indonesia - Inang Ayu; Suryaningsi; Indah Zakiyah (Jurnal Akuntansi Universitas Muhammadiyah Kupang, 2023)
This research was conducted on LQ45 companies listed on the Indonesia Stock Exchange for the 2019-2021 period. The type of research used by the author is the quantitative method, the sampling method uses purposive sampling, and the data source used is secondary data, which comes from the company's audited financial statements LQ45. The number of samples in this study were 30 companies. Auditor switching in this study uses din variable proxies. The data analysis technique used is Descriptive Statistical Analysis and Multiple Linear Regression Analysis. This research was conducted at the Indonesia Stock Exchange Office. Based on the results of the descriptive statistical tests, the F test, and the T test, the results showed that financial distress, management changes, and client company size had no effect either partially or simultaneously on auditor switching.